EVALUASI IMPLEMENTASI SISTEM INFORMASI PAKET APLIKASI SEKOLAH MENGGUNAKAN FRAMEWORK COBIT - Stabit Handoyo; Bambang Soedijono WA; Emha Taufiq Luthfi (Politeknik Indonusa Surakarta, 2018)
This study discusses about School Information System Application Package Audit Using Cobit Framework implemented in SMK Negeri 2 Gedangsari. This study aims to measure the maturity level of the selected process that is DS4 and DS8 in SIM applications that have been applied in SMK Negeri 2 Gedangsari and to prepare recommendations as input for school management after getting the results of measurement maturity level Management Information Systems. The focus of this research is 1 domain of Cobit 4.1 which is the DS (Delivery and Support)domain, Especially DS04 and DS08. Data collection is done by distributing questionnaires, interviews and observations directly. The three methods are based on COBIT 4.1 model. The results of data processing will be used to find the weaknesses contained in each domain. The findings of weakness or problem will be compared with ideal conditions that have been set COBIT 4.1 at each level, so that the suitable recommendation can be applied. Based on the results of calculations on each IT process contained in the domain Delivery and Support (DS), the maturity level is at level 2 (repeatable), so that to achieve the desired maturity level at level 3 (defined process) then all procedures required in each process must be met. To achieve level 3 (defined process), every IT process must have standardized and written procedures that socialized to all parties involved in academic information system, that is to system manager and user. Such procedures should be documented and updated on a regular basis.